Stacking Order-Dependent Electronic and Optical Properties of h-BP/Borophosphene Van Der Waals Heterostructures - Kejing Ren; Quan Zhang; Shengli Zhang; Yang Zhang (Nanomaterials)
Van der Waals (vdW) heterostructures, typically composed of two-dimensional (2D) atomic layers, have attracted significant attention over the past few decades. Their performance is closely dependent on their composition and interlayer interactions. In this study, we constructed four types of 2D hexagonal BP monolayer (h-BP)/borophosphene vdW heterostructures with different stacking orders: (i) B-B stacking, (ii) P-P stacking, (iii) moire-I, and (iv) moire-II. Their structural stability and their electronic and optical properties were explored by using first-principles calculations. The results show that h-BP/borophosphene heterostructures can maintain their configurations with good structural stability and minimal lattice mismatch. All vdW heterostructures exhibit semiconducting characteristics, and their band gaps are highly dependent on interlayer stacking orders. Due to the regular atomic arrangement and enhanced interlayer dipole interactions, the B-B stacking bilayer opens a relatively large band gap of 0.157 eV, while the moire-II bilayer exhibits a very small band gap of 0.045 eV because of its irregular atom arrangements. By calculating the complex dielectric function, optical absorption spectra of B-B and P-P stacking bilayers were discussed. This study suggests that h-BP/borophosphene heterostructures have desirable optical properties, broadening the potential applications of the constituent monolayers.